Left Dorsolateral Prefrontal Cortex rTMS in Alleviating MTBI Related Headaches and Depressive Symptoms. Issue 4 (30th May 2017) - Leung, Albert; Metzger‐Smith, Valerie; He, Yifan; Cordero, James; Ehlert, Brandon; Song, David; Lin, Lisa; Shahrokh, Golshan; Tsai, Alice; Vaninetti, Michael; Rutledge, Thomas; Polston, Greg; et al.
Abstract : Objective: Persistent mild traumatic brain injury related headache (MTBI‐HA) represents a neuropathic pain state. This study tested the hypothesis that repetitive transcranial magnetic stimulation (rTMS) at the left prefrontal cortex can alleviate MTBI‐HA and associated neuropsychological dysfunctions. Methods and Materials: Veterans with MTBI‐HA were randomized to receive four sessions of either real (REAL group) or sham (SHAM group) high frequency rTMS delivered at 10 Hz, 80% of resting motor threshold and 2000 pulses per session at >24 and <72 hours apart. Pre‐treatment, post‐treatment 1‐week and 4‐week headache and neuropsychological assessments were conducted. Results: Twenty nine out of forty‐four consented subjects completed the study. A two‐factor (visit × treatment) repeated measures ANOVA showed a significant ( p = 0.002, F = 11.63, df = 1) interaction for the average daily persistent headache intensity with the REAL group exhibiting a significant ( p < 0.0001) average reduction (±SD) of 25.3 ± 16.8% and 23.0 ± 17.7% reduction in their numerical rating scale at the one‐week and four‐week post‐treatment assessments in comparison to <1 ± 11.7% and 2.3 ± 14.5% reduction found in the SHAM group. In addition, a significant ( p < 0.01) 50% and 57% reduction was found in the prevalence of persistent headache in the REAL group at the one‐week and four‐week assessments in comparison to 7% and 20% reduction found in the SHAM group. Furthermore, the REAL group demonstrated a significant ( p = 0.033) improvement (from 22.3 ± 6.4 at pre‐treatment to 19.0 ± 5.0 at post‐treatment one‐week) in the Hamilton Rating Scale for Depression score, while the SHAM group's score remained largely unchanged (from 25.33 ± 8.43 to 24.64 ± 5.03) in the same time frame. This trend of improvement, although not statistically significant, continues to the post‐treatment four‐week assessment. Conclusion: A short‐course rTMS at the left DLPFC can alleviate MTBI‐HA symptoms and provide a transient mood enhancing benefit. Further studies are required to establish a clinical protocol balancing both treatment efficacy and patient compliance.